Optimalisasi Sistem Informasi Manajemen Bisnis pada UMKM di Rantauprapat Kabupaten Labuhanbatu dalam Mendukung Transformasi Digital - Siregar, Habibatul Jannah; Br. Pohan, April Yanti; Yusuf, Muhammad; Sudaryat, Rahmat; Sumitro, Sumitro (Jurnal Manajemen Akuntansi (JUMSI), 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Rantauprapat, Labuhanbatu Regency play an essential role in local economic development. However, most MSMEs still rely on manual systems and lack digital adaptation. This study investigates the implementation of Business Management Information Systems (BMIS) in local MSMEs and evaluates its impact on operational performance, efficiency, and competitiveness. Using a qualitative descriptive method, data were collected from 5 MSME owners through interviews, field observations, and documentation. The results indicate that BMIS adoption significantly enhances inventory management, sales tracking, and financial recording. Nevertheless, challenges such as limited digital literacy and infrastructure gaps remain. The study concludes with recommendations for digital training programs and local government support to foster sustainable technological integration in Labuhanbatu's MSME sector.